The Death Penalty from a Criminal Law Perspective: Between the Deterrent Effect, Morality, and Human Rights - Muhammad Syaifudin Hisbullah; Elly Trisnawati; Ana Krisdiyana; Valencia Angel; Eko Budi (Jurnal Ilmiah Dunia Hukum, 2025)
This article examines the complexities of the death penalty in Indonesia, emphasizing three key aspects: its effectiveness as a crime deterrent, its moral and ethical legitimacy, and its compliance with human rights and international obligations. The study employs a normative-juridical approach with descriptive analysis, combining legislative and conceptual approaches to examine the Criminal Code, the Narcotics Law, court decisions, academic literature, and international publications. The analysis shows that the effectiveness of the death penalty as a deterrent remains debated, as social, economic, educational, and environmental factors often play a greater role in determining criminal behavior than the threat of physical punishment. From a moral and human rights perspective, the death penalty poses a dilemma between the utilitarian principle, and the deontological principle. Constitutional Court and Supreme Court decisions, as well as Law Number 1 of 2023, emphasize selectivity, proportionality, probation, and a restorative approach as an effort to balance the interests of the public, victims, and perpetrators. The Islamic legal approach through qisas and diyat also offers a humanistic restorative alternative. Thus, the death penalty in Indonesia must be implemented fairly, selectively, and humanely, in accordance with legal ethics, human rights principles, and the values of social justice.